Platytomus pittinoi Minkina & Byk, a new species of Psammodiini (Coleoptera: Scarabaeidae: Aphodiinae) from Greece - Minkina, Łukasz; Byk, Adam; Nowak, Cezary; Bidas, Marek; Mokrzycki, Tomasz (Zootaxa, 2023)
Platytomus pittinoi Minkina & Byk, a new species of Psammodiini (Coleoptera: Scarabaeidae: Aphodiinae) from Greece is described and illustrated. Newly described species is compared to the morphologically most similar species Platytomus laevistriatus (Perris, 1870).